DAMPAK PENGELOLAAN OBJEK WISATA BONO TERHADAP KEBERDAYAAN EKONOMI MASYARAKAT - Safitra, Ahmad Rizki; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Reseach on the impact of Bono tourism management on community economic empowerment. Is an activity carried out to strive for something to better and solve  problems contained in the management of Bono attractions that is not the government in the mangement of Bono atrractions and inadequate facilities and infrastructure, the purpose of this study was to determine the impact of Bono tourism object management on the economic empowerment of the community and to find out what factors hinder Bono tourism object management. the study uses the concept of quoting theory from Sujianto (2009) explaining that there are 5 discourses of development in comunity empowerment namely independence, partisipative, networking, justice and sustainability. The outhor uses qualitative reseach methods by studying data descriptively. In collection data reseachers used interview, observation, and documentation techiques. From the results of this study it can be seen that the impact of Bono attraction  mangement on the economic empowerment of the community has not been managed properly. there are still many facilities and infrastructure that have not been properly managed.Keywords : Management, Empowerment